Effects of (Cr0.5Ta0.5)4+ on structure and microwave dielectric properties of Ca0.61Nd0.26TiO3 ceramics. Issue 7 (May 2018) - Xiong, Zhe; Tang, Bin; Fang, Zixuan; Yang, Chengtao; Zhang, Shuren
Abstract: The Ca0.61 Nd0.26 Ti1- x (Cr0.5 Ta0.5 ) x O3 (CNT-CT x ) ceramics with orthorhombic perovskite structure were prepared using the conventional solid-state method. The X-ray diffraction (XRD), Raman spectra and X-ray photoelectron spectra (XPS) were employed to investigate the correlations between crystal structure and microwave dielectric properties of CNT-CT x ceramics. The XRD results showed that all CNT-CT x samples were crystallized into the orthorhombic perovskite structure. The SEM micrographs indicated that the average grain size of samples depended on the sintering temperature. As (Cr0.5 Ta0.5 ) 4+ concentration increased, there was a significant decrease in the average grain size of samples. The short range order (SRO) structure and structural distortion of oxygen octahedra proved to exist in CNT-CT x crystals according to the analysis of Raman spectra results. The microwave dielectric properties highly depended on the full width at half maximum (FWHM) of Raman spectra, oxygen octahedra distortion, reduction of Ti 4+ to Ti 3+ and bond valence. At last, the CNT-CT0.05 ceramic sintered at 1420 °C for 4 h exhibited the good and stable comprehensive microwave dielectric properties: relative permittivity of 96.5, quality factor of 14, 360 GHz, and temperature coefficient of resonant frequency of +153.3 ppm/°C.